Identity or Condition: The Theory and Practice of Applying State Disability Laws to Transgender Individuals - Chung, Jeannie J. (Columbia Journal of Gender and Law, 2011)
Jean Doe was a 17-year-old transgender youth when she brought suit against the New York City Administration for Children’s Services in New York Supreme Court. She had been in and out of foster homes since the age of nine, and had a troubled history of “violent altercations” in many of the foster homes in which she had been placed throughout these years. Her latest placement was in the Atlantic Transitional Foster Facility, an all-male facility for short-term placement of foster children who are in the care of New York City’s Administration for Children’s Services. Upon her arrival at Atlantic Transitional, the director of the facility expressly prohibited her from expressing her gender identity by wearing “female attire,” although she still could wear “scarves, ‘nails,’ brassieres, and enhancers.” When Jean Doe moved for a preliminary injunction, Atlantic Transitional tried to avoid liability by broadening its policy’s reach to the rest of the facility, forbidding all residents from wearing skirts or dresses. Undeterred, Doe brought a lawsuit against the facility, alleging gender discrimination, violations of her First Amendment to free expression, and disability discrimination. The court ultimately found for Doe solely on the disability discrimination claim and mentioned nothing about the other two claims in its opinion. Doe v. Bell is illustrative of the difficulties transgender advocates have had in bringing gender discrimination claims on behalf of their clients, as well as their relative success in using state disability anti-discrimination laws to garner protection for their clients. Cases that recognize gender discrimination laws as inclusive of transgender individuals, have changed the legal landscape for transgender individuals, such as the recent D.C. Circuit case of Schroer v. Billington, which held that a transgender plaintiff had been discriminated against in employment on the basis of sex under Title VII of the 1964 Civil Rights Act. In many cases over the past two decades, advocates have demonstrated the efficacy of state disability anti- discrimination claims as applied to transgender individuals. Although federal law expressly excludes transgender individuals from the protected class of persons with disabilities, many states do not follow suit. Moreover, at least one State court used the federal exclusion to show that the absence of this exclusion in that State’s disability laws clearly demonstrated the State legislature’s intent to actively include transgender individuals under these laws.